Analisis Pengendalian Kualitas dengan Menggunakan Metode Fault Tree Analysis (FTA) dan Failure Mode and Effect Analysis (FMEA) untuk Mengurangi Produk Cacat Klem Accu di IKM Geulis Automotif - Yunita, Dea Rahma; Ulum, Rikzan Bachrul; Wibowo, Priyo Ari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
his study aims to identify and reduce defects in battery clamp products at Geulis Automotif SME by applying Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) methods. Defect data from January to December 2024 show an average defect rate of 10.74%, with the most dominant types being dents and holes. FTA was used to systematically identify root causes, while FMEA evaluated risk levels using the Risk Priority Number (RPN). The highest RPN value reached 160, caused by poor-quality solder material. The analysis produced improvement recommendations including raw material inspection, solder filtering, mold maintenance, and enhancing operator focus through task rotation and daily briefings. The combined use of FTA and FMEA proved effective in minimizing failure risks and improving the overall quality of battery clamp production.